Strategi Kebijakan Penguatan Ketersediaan Pangan (Food Availability) Untuk Mewujudkan Ketahanan Pangan Kota Sukabumi - Nina Wardhani (Jurnal Agribisnis dan Pembangunan Pertanian (JAPP), 2026)
The impact of miscarriage Sukabumi's City Food Security Index in 2025 causing a potential for future food insecurity. This is driven by low food availability, resulting from a low ratio of consumption to staple food availability due to limited supplies, which ultimately led to the target shortfall of the 2025 Food Security Index. Strengthening Sukabumi City's food security in terms of staple food availability can be pursued through several policy alternatives: (1) Existing Land Intensification Policy; (2) Sustainable Food Agricultural Land Policy (LP2B); (3) Strategic Food Reserve Policy; (4) Supply-side Management Policy; (5) Food Loss and Waste Reduction Policy; and (6) Local Food Processing Policy. Based on the keyperson method, the Supply-side Management Policy implemented through Hinterland Supply Agreements, a City Food Balance Early Warning System, and the Strengthening of City Food Logistics and Distribution Systems was identified as the selected alternative, deemed the most effective, efficient, and impactful. This paper provides comprehensive policy recommendations to support food security enhancement that can be implemented by the local government and relevant stakeholders.